Drug resistance patterns of bacteria isolated from patients with nosocomial pneumonia at Tehran hospitals during 2009-2011 - Mehri Haeili; Arash Ghodousi; Bijan Nomanpour; Maryam Omrani; Mohammad Mehdi Feizabadi (Journal of Infection in Developing Countries)
Introduction: Nosocomial pneumonia remains an important cause of mortality and morbidity worldwide. Surveillance programs play an important role in the identification of common etiologic agents and local patterns of antimicrobial resistance.